Evolving Financial Reporting Practices: A Comparative Study of the Nordic Countries' Harmonization Efforts* - MONSEN, NORVALD; WALLACE, WANDA A. (Contemporary Accounting Research, 1995)
Abstract. In the 1960s, a group of culturally similar countries—the Nordic countries—cooperated in harmonizing their companies acts, including their accounting requirements. They even issued a Nordic proposal for new companies acts, intended to be enacted as new laws in each of the Nordic countries. The purpose of the paper is to study this harmonization effort and to suggest future research to enhance our understanding of diverse financial reporting practices. The paper shows that accounting harmonization in this context was difficult, even though the prerequisites for success were excellent. Future research should explore the experiences of accounting harmonization in other contexts. Résumé. Dans les années 60, un groupe de pays de même parenté culturelle — les pays nordiques — ont collaboré à l'harmonisation de leurs lois sur les sociétés ainsi que de leurs exigences en matière comptable. Ils ont même produit une Proposition des pays nordiques relative à de nouvelles lois sur les sociétés, qui devaient être sanctionnées dans chacun des pays participants. Les auteurs ont ici pour but d'analyser cet effort d'harmonisation et de suggérer d'éventuels travaux de recherche qui nous amèneraient à mieux comprendre différentes pratiques en matière d'information financière. Les auteurs expliquent que l'harmonisation comptable, dans ce contexte, s'est révélée difficile, même si les préalables au succès étaient excellents. Les travaux de recherche à venir devraient porter sur l'analyse des expériences d'harmonisation comptable dans d'autres contextes.